2001
DOI: 10.1021/es001940m
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Respirable Particulate Matter Concentrations from an Open Fire, Improved Cookstove, and LPG/Open Fire Combination in a Rural Guatemalan Community

Abstract: Improved biomass cookstoves have the potential to reduce pollutant emissions and thereby reduce pollution exposure among populations in developing countries who cook daily with biomass fuels. However, evaluation of such interventions has been very limited. This article presents results from a study carried out in 30 households in rural Guatemala. Twenty-four hour PM3.5 concentrations were compared over 8 months for three fuel/cookstove conditions (n = 10 households for each condition): a traditional open fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 18 publications
(27 reference statements)
8
111
2
2
Order By: Relevance
“…According to anthropological information, the mothers might use tobacco occasionally as a medicine against certain health problems. Our baseline data from the study villages found that less than 2% of the women admitted to ever having smoked, and the fathers who did smoke did not do so at home (Albalak et al, 2001). A survey in a neighboring Mam-speaking area (Grajeda et al, 1994) did not identify a single mother who admitted to be a smoker.…”
Section: Key Information From Other Preparatory Studiesmentioning
confidence: 81%
See 4 more Smart Citations
“…According to anthropological information, the mothers might use tobacco occasionally as a medicine against certain health problems. Our baseline data from the study villages found that less than 2% of the women admitted to ever having smoked, and the fathers who did smoke did not do so at home (Albalak et al, 2001). A survey in a neighboring Mam-speaking area (Grajeda et al, 1994) did not identify a single mother who admitted to be a smoker.…”
Section: Key Information From Other Preparatory Studiesmentioning
confidence: 81%
“…The majority of the families in the area are subsistence farmers, earning some cash supplement from selling their agricultural products at the local markets. Infant mortality rates are estimated to be approximately 55/1000 live births, and ARI are the leading cause of death (Albalak et al, 2001). Typical homes are made of simple adobe walls (bricks made of dried dirt), dirt floors and tile or metal roofs.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations